A multi-scale self-consistent model describing the lattice deformation in austenitic stainless steels. (1st January 2016) - Hu, Jianan; Cocks, Alan C.F.
Abstract: Differently oriented grains within a polycrystalline material exhibit different micro-mechanical lattice responses for a given macroscopic stress due to the local elastic and plastic anisotropy. A physical understanding of the lattice deformation mechanism during plastic flow is still lacking. In this study, a three-dimensional multi-scale self-consistent model is developed to examine the micro-mechanical deformation behaviour of F.C.C. polycrystalline austenitic stainless steels under uniaxial tensile loading at ambient temperature. The model is formulated in a crystal based plasticity framework and takes into account the detailed kinematics of dislocation slip and its influence on the evolution of the dislocation distribution on different crystallographic planes of individual grains within a polycrystalline material. The effect of athermal solute strengthening is also incorporated. Predictions of the microscopic lattice response developed within individual grains are compared with various available experimental results obtained using neutron diffraction (ND). There are significant differences in the way in which the lattice strain evolves with macroscopic strain obtained by different groups. This is explained in terms of the variation in initial residual stress state in the samples tested by these different groups.